Identificación de las principales plagas que afectan al cultivo de Fresa (Fragaria vesca) en tres zonas agroecológicas del cantón Quito, provincia de Pichincha - Tamba Sandoval, Juan Enrique (2015)
In research study. Identification of the main pests affecting the crop of strawberry (Fragariavesca) in three agro-ecological zones of the canton Quito, Pichincha Province. Whose objectives were to recognize the most common pests in strawberry cultivars Czech Yaruquí and Pifo. Identify the growth stages of the crop that is most affected. Propose alternative control major pests. The technique used was the interview with the help of a questionnaire. Analysis by descriptive statistics and use Microsoft Excel. The main results are: the 3 zones investigated ecological agro 100% literate, facilitating training and management technology for the management of pests and diseases in strawberry cultivation. Most strawberry farmers lease their land for farming. lease cost between $ 2000 and $ 2500 hectare per year these areas are considered very good for strawberry production as they are flat and mostly all have irrigation water. The site preparation is done mechanically, using machinery and agricultural tractors and power tillers. Soil disinfection is done in Czech by 92%; in Yaruquí the 97.50% and 76.47% Pifo one; producers make this work prior to planting to prevent pests with the use of agrochemicals as clortirifox. The main pests affecting the crop in the area of Czech; Yaruquí and Pifo in order of importance are: the highest incidence is red mite (mite) (Tetranychusurticae); followed Thrips (Frankliellaoccidentalis); then aphids (aphids) (Chaetosiphonfragaefolii); then slugs (Arionhortensis) and the lowest incidence in the genre. Hopliacallipyge (white grubs, or cutzos) The phenological stages strawberry crop more susceptible to insect attack in order of importance alike in Czech; Yaruquí and Pifo are: Transplantation; seedling development; fruit ripening and the beginning of flowering stage is the least affected the fruit set In the three study areas pest control is what makes mostly by chemical methods (Czech, 80%; Yaruqui Pifo 93.33% and 82.35%). The ecological control (Czech, 16%; Yaruqui Pifo 5.83% and 11.76%). this is less often and finally the least used is the (Czech, 4%, 5% Yaruqui Pifo 5.88%) physical control. Within the chemical control is done with chlorpyrifos, carbosulfan; profenosl; Piriproxyfec, among others; for ecological control is performed with the addition of organic matter, crop rotation and use of biological agents beneficial physical control in do so by manually removing and destroying insects and trapping